Diseño e implementación de procedimientos de control físico y contable de propiedad, planta y equipo para la Empresa “Talleres Faconza” en base a la NIC 16 y la NIC 12 - Aguiar Aldaz, Adriana Margoth (2014)
This paper aims to establish accounting procedures both as physical applicable to property, plant and equipment (PP & E) Workshop Faconza, for which we have defined three chapters, which are presented below.